Effect of NR-g-cellulose coupling agent into NR-cellulose composite dispersibility and its physical properties. (November 2019) - Handayani, H; Cifriadi, A; Handayani, A S; Chalid, M; Savetlana, S; Christwardana, M
Abstract: Natural rubber and cellulose are two materials with very different compatibility, so it is difficult to produce homogenous composite without using coupling agent. Natural rubber is nonpolar while cellulose is polar. The combination of natural rubber with cellulose is expected to produce composite with higher strength. The reinforcement concept of polymeric materials, such as natural rubber with cellulose as filler, results from increased rubber-filler interactions. This study aims to determine the effect of NR- g -Cellulose as coupling agent on the dispersibility of the composite and its physical properties. Hexamine/resorcinol and silane were used as a reference for a commercial coupling agent. Cellulose material was mixed in two-roll open mill together with natural rubber and other chemicals using three types of coupling agents, hexamine/resorcinol, silane, and NR- g -Cellulose. The FESEM result of the surface of composite indicated that composite with NR- g -Cellulose as coupling agent showed homogenously dispersed compared to two other types of coupling agent but it is lower in physical properties, especially in tensile strength, tear strength, compression set, and rebound resilience of the composite. It may be caused by the NR- g -Cellulose coupling agent not working optimally and therefore it needs a high temperature to optimize the coupling agent to react with natural rubber and cellulose.